2014
DOI: 10.4315/0362-028x.jfp-13-220
|View full text |Cite
|
Sign up to set email alerts
|

Use of Enterococcus faecium as a Surrogate for Salmonella enterica during Extrusion of a Balanced Carbohydrate-Protein Meal

Abstract: Multiple outbreaks of salmonellosis have been associated with the consumption of low-moisture products, including extruded products. Therefore, there is a need for a nonpathogenic, surrogate microorganism that can be used to validate extrusion processes for Salmonella. The objective of this research was to determine if Enterococcus faecium NRRL B-2354 is an adequate surrogate organism for Salmonella during extrusion. Extrusions at different temperatures were done in material contaminated with both organisms. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 20 publications
(19 reference statements)
2
33
1
Order By: Relevance
“…Similar results were also observed by Himathongkham and others () and Bianchini and others () for inactivation of the pathogen, Salmonella Enteritidis, and Enterococcus faecium , a common surrogate test organism for Salmonella , during extrusion of feed. However, Bianchini and others () reported that the Salmonella population in a balanced carbohydrate–protein meal typical of an extruded pet food formula at 28% moisture was reduced by 5 log CFU/g at just 60.6 °C, which conflicts with the findings of our study and a study by Walsh and Funke () that demonstrated a 1‐log reduction of Staphylococcus aureus during low‐temperature extrusion (35 to 55 °C) of spaghetti at an initial moisture content of 31.5%. Our results also differ with those obtained by Ukuku and others () who demonstrated that corn meal and whey protein isolate extruded at 55 °C with a w of 0.98 to 0.99 (35.5% to 42.1% moisture content) resulted in greater than 5‐log and 4‐log reductions of Escherichia coli , respectively, and Quéguiner and others () who found that temperatures over 130 °C were necessary to achieve a greater than 4‐log reduction of Streptococcus thermophiles in whey powder having a very low initial moisture content (4% to 5%).…”
Section: Resultscontrasting
confidence: 99%
“…Similar results were also observed by Himathongkham and others () and Bianchini and others () for inactivation of the pathogen, Salmonella Enteritidis, and Enterococcus faecium , a common surrogate test organism for Salmonella , during extrusion of feed. However, Bianchini and others () reported that the Salmonella population in a balanced carbohydrate–protein meal typical of an extruded pet food formula at 28% moisture was reduced by 5 log CFU/g at just 60.6 °C, which conflicts with the findings of our study and a study by Walsh and Funke () that demonstrated a 1‐log reduction of Staphylococcus aureus during low‐temperature extrusion (35 to 55 °C) of spaghetti at an initial moisture content of 31.5%. Our results also differ with those obtained by Ukuku and others () who demonstrated that corn meal and whey protein isolate extruded at 55 °C with a w of 0.98 to 0.99 (35.5% to 42.1% moisture content) resulted in greater than 5‐log and 4‐log reductions of Escherichia coli , respectively, and Quéguiner and others () who found that temperatures over 130 °C were necessary to achieve a greater than 4‐log reduction of Streptococcus thermophiles in whey powder having a very low initial moisture content (4% to 5%).…”
Section: Resultscontrasting
confidence: 99%
“…faecium has been used as a surrogate for Salmonella in various thermal lethality studies, including dry heating of peanuts, moist-air heating of almonds, thermal inactivation in liquid products, and extrusion (1,2,10,18,19). E. faecium was used for the present study because it is easy to recover from contaminated surfaces and feed using selective and differential media.…”
Section: Resultsmentioning
confidence: 99%
“…E. faecium NRRL B-2354 has been established as a surrogate for Salmonella for the validation of thermal processes to ensure a 4-to 5-log reduction of Salmonella in almonds (1,5, 27f this organism is also regarded as a suitable surrogate for foodbome pathogens in thermal processing of other nuts, dairy products, juices, and meat, and it has been extensively used in validation studies for different low-moisture food products, including almonds, walnuts, peanut butter, extruded products (i.e. carbohydrate-protein meal), and others (1,3,4,6,29,32,34). Ma et al (29) demonstrated that the heat resistance of E. faecium NRRL B-2354 was consistently and significantly greater (17.7 times) than that of Salmonella in ground beef, raising the concern that the surrogate may overly exceed the heat resistance of the target pathogen; therefore, its use in thermal process validation may result in overprocessing and higher energy costs (29).…”
Section: Resultsmentioning
confidence: 99%